Micro-HBI: Human-Biology Interaction With Living Cells, Viruses, and Molecules - Lee, Seung Ah; Riedel-Kruse, Ingmar H. (Frontiers in Computer Science, 2022)
Human-Biology Interaction (HBI) is a field that aims to provide first-hand experience with living matter and the modern life sciences to the lay public. Advances in optical, bioengineering, and digital technologies as well as interaction design now also enable real and direct experiences at the microscale, such as with living cells and molecules, motivating the sub-field of 'micro-HBI'. This is distinct from simulating any biological processes. There is a significant need for HBI as new educational modalities are required to enable all strata of society to become informed about new technologies and biology in general, as we face challenges like global pandemics, environmental loss, and species extinctions. Here we review this field in order to provide a jump-off point for future work and to bring stakeholder from different disciplines together. By now, the field has explored and demonstrated many such interactive systems, the use of different microorganisms, new interaction design principles, and versatile applications, such as museum exhibits, biotic games, educational cloud labs, citizen science platforms, and hands-on do-it-yourself (DIY) Bio maker activities. We close with key open questions for the field to move forward.